Correlation Between the Presence of Antinuclear Antibodies and Recurrent Pregnancy Loss: A Mini Review - Liu, Ting; Guo, Xi; Liao, Ying; Liu, Yingyu; Zhu, Yuanfang; Chen, Xiaoyan (Frontiers in Endocrinology, 2022)
In the past decade, the incidence of recurrent pregnancy loss (RPL) has increased significantly and immunological disorder has been considered as one of the possible causes contributing to RPL. The presence of antinuclear antibodies (ANAs) is regarded as a typical antibody of autoimmunity. However, the relationship between the presence of ANAs and RPL, the underlying mechanism and the possible role of immuno-therapy are still controversial. The aim of this mini review is to assess the association between ANAs and RPL and the effects of immuno-therapy on pregnancy outcomes in women with positive ANAs and a history of RPL from the available data, so as to provide relevant reference basis for clinical application in this group of women.